The utility of rasch measurement for learning environments research - Cavanagh, Rob; Waugh, R. (Sense Publishers, 2011)
The purpose of this introductory chapter is to show in simple ways, how using a Rasch model can benefit learning environments research. As such, it is deliberately non-technical and written for readers who do not wish to pursue complex mathematical matters either now, or perhaps not even later. There are many established instructional courses and texts on applying the Rasch model and we assume that researchers requiring a more formal and theoretical understanding will consult these (for example, Bond & Fox, 2007). The chapter is structured into a series of sections each dealing with a particular aspect of the model or its application. The first section is about measurement in the human sciences.